EFFECTS OF GLOBAL FINANCIAL CRISIS IN DEVELOPED AND EMERGING FINANCIAL MARKETS - Нермина Побрић (Acta Economica, 2011)
The influence of the crisis on developed, developing and emerging market countries will come through real and financial sectors. While the transmission mechanisms through trade are straightforward, those through financial channels appear to be more challenging as financial linkages have been more complicated than international trade.